2012
DOI: 10.1016/j.bmcl.2012.09.104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of colchicine C-ring analogues tethered with aliphatic linkers suitable for prodrug derivatisation

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The Suzuki cross-coupling reaction was performed between this series of protected bromides 27−32 and 3,4,5-trimethoxyphenylboric acid (8) to obtain compounds 33−38.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…The Suzuki cross-coupling reaction was performed between this series of protected bromides 27−32 and 3,4,5-trimethoxyphenylboric acid (8) to obtain compounds 33−38.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…The assembly and disassembly of aand b-tubulins lead to polymerization of microtubules, and it is very important for chromosomal segregation during mitosis. Since anticancer activity of vinca alkaloids (e.g., 1 and 2), colchicine (3), and paclitaxel (4) are attractive to chemists and biologists, several derivatives of these drugs have been prepared and investigated for anticancer activity [19][20][21][22][23][24][25][26][27]. Cancer cell growth can be inhibited either by the inhibition of tubulin polymerization or the promotion of tubulin polymerization.…”
Section: Tubulin/microtubule-targeted Anticancer Agentsmentioning
confidence: 99%
“…A phase II clinical trial of 17-AAG (22) showed a significant anticancer activity in patients with HER2-positive metastatic breast cancer [65]. Recently, 19-substituted geldanamycin derivatives (24)(25)(26)(27)(28)(29) were synthesized ( Fig. Although several semisynthetic geldanamycin derivatives were prepared and evaluated for Hsp90 inhibitory activity, the structure modifications were mostly performed at the C-17 position of 21.…”
Section: Heat Shock Protein 90 Inhibitors As Anticancer Agentsmentioning
confidence: 99%
“…Although Col is not used clinically to treat cancer due to its toxicity, it does exert anti-proliferative effects through the inhibition of microtubule formation leading to mitotic arrest and cell death by apoptosis. However, it has also been shown to produce anti-vascular effects [8] leading to a greater reduction of blood flow in tumors than in normal tissues and the ability to overcome P-glycoprotein efflux pump mediated multidrug resistance [9], which renders Col a model molecule for the development of a series of novel anticancer drugs with a better toxicological profile [1,[10][11][12][13], many of them currently undergoing clinical studies. Nevertheless, as a downside, it has also been reported that the central administration of cytoskeletal poisons, such as Col, causes oxidative stress in animals leading to cognitive impairment [14], and its therapeutic use has been linked to sporadic Alzheimer's disease in humans [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it has also proven its efficiency in the treatment of Mediterranean fever, Behçet's syndrome, scleroderma, amyloidosis, liver cirrhosis, but also other comorbid conditions associated with gout, such as osteoarthritis and various cardiovascular diseases [1,2]. Col demonstrates a multimodal mechanism of action and continues to be in the focal point of the very recent biomedical, clinical and toxicological research [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%